Analisis Faktor Eksternal yang Berpengaruh terhadap Produksi Ayam Broiler Di Kabupaten Gianyar Provinsi Bali - Fita Selia; I. Gusti Agus Maha Putra Sanjaya; I Gusti Ayu Dewi Seri Rejeki (GEMA AGRO, 2024)
The increasing demand for broiler chickens occurs because the shift in people's consumption patterns from food sources of vegetable protein to food sources of livestock protein is expected to continue to increase and continue in the future. One of the factors that can influence the success of broiler chicken production is external factors, where external factors include chicken seeds (DOC), death/mortality rates, feed, labor and marketing. The aim of this research is to find out whether external factors of breeders have an influence on broiler chicken production in Gianyar Regency, Bali Province and to find out what indicators of external factors of breeders have the most dominant influence on broiler chicken production in Gianyar Regency, Bali Province. The population of this study were all broiler chicken breeders who live in Gianyar Regency, Bali Province. The number of samples for this research was 57 samples taken using the purposive random sampling method. The design used in this research was a survey method. In this research, the data collection method used was a questionnaire. Data collection was carried out by means of interviews, observations and questionnaires. The collected data was analyzed using qualitative descriptive analysis. The research results show that from the T test results, DOC (X1), Feed (X3), Labor (X4), and Marketing (X5) which are indicators of the External Factor variable (X) are proven to have no significant effect on the Broiler Chicken production variable ( Y). And the mortality rate indicator (X2) is the most dominant indicator and has a significant effect on Broiler Chicken Production (Y).